Qualidade pós-colheita do fruto caqui (DIOSPYRUS KAKI L.) , CV. FUYU, produzido em Porto Amazonas – Pr - Silva, Luciane Curtes Porfírio da (2008)
Refrigerated storage is the main technology for maturity control and for minimizing deterioration of the fruit. However, because kaki (‘Fuyu’) is sensitive to cold temperatures, it can develop physiological disorders depending on the temperature and period of storing. Thus, considering its commercial value, this study aims to contribute with knowledge related to its postharvest quality. Commercial product Promalin® was applied to a plant sample of the fruit whereas another sample did not receive the product. The harvested fruit were stored in cold chamber (4ºC, commercial use) and in room temperature (20 to 26 ºC). The quality loss of the fruit was monitored during the storage. The cold chamber kept good fruit firmness quality for commercialization over 16 days, for both treatments, without and with the Promalin® application in the orchard, while in room temperature the periods were 16 and 8 days respectively. And Promalin® contributed for the bettering of firmness of these stored fruit, during the same time period, in the cold chamber. The Promalin® product anticipated the loss of firmness at room temperature compared to fruit that did not receive this product, and the activity of the poligalacturonase (PG) enzyme was coincident. The enzyme activity was coincident, whereas to what concerned to the poliphenoloxidase (PFO) enzyme, as long as the fruit presented acceptable firmness for its commercialization in cold chamber, there were not significant changes in its activity neither in those fruit without Promalin® nor in those which received the application of this product in the orchard. The total soluble solids, measured as °Brix, did not suffer significant change during its storage in cold chamber.